Tonoplast intrinsic proteins and vacuolar identity. (24th May 2010) - Gattolin, Stefano; Sorieul, Mathias; Frigerio, Lorenzo
Abstract : TIPs (tonoplast intrinsic proteins) have been traditionally used as markers for vacuolar identity in a variety of plant species and tissues. In the present article, we review recent attempts to compile a detailed map of TIP expression in Arabidopsis, in order to understand vacuolar identity and distribution in this model species. We discuss the general applicability of these findings. We also review the issue of the intracellular targeting of TIPs and propose key emerging questions relative to the cell biology of this protein family.